2020
DOI: 10.21037/atm-20-1695
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of factors affecting the visualization of dye after transbronchial dye injection: an animal experiment

Abstract: Background: Since peripheral lung lesions can be frequently visualized on computed tomography (CT), various methods of localization for thoracoscopic surgery have been developed. In the case of transbronchial dye injection (TDI), there can be difficulties with dye visualization through the thoracoscope depending on early disappearance of the dye due to diffusion before field exposure. Herein, we performed an animal experiment to determine the appropriate dye amount and the duration of visualization.Methods: Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“… 1 , 2 We have previously reported that transbronchial injection of a dye mixture of indigo carmine and Lipiodol can be a good method for preoperative marking of the visceral pleura. 11 , 15 In the present study, using a porcine model, we demonstrated that this dye mixture, injected using a bronchoscope and spray catheter, remained on the visceral pleura for up to 24 h and could be detected with the naked eye. To the best of our knowledge, this is the first study to evaluate the stability of a dye for preoperative marking of the visceral pleura.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“… 1 , 2 We have previously reported that transbronchial injection of a dye mixture of indigo carmine and Lipiodol can be a good method for preoperative marking of the visceral pleura. 11 , 15 In the present study, using a porcine model, we demonstrated that this dye mixture, injected using a bronchoscope and spray catheter, remained on the visceral pleura for up to 24 h and could be detected with the naked eye. To the best of our knowledge, this is the first study to evaluate the stability of a dye for preoperative marking of the visceral pleura.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, precise localization of lung nodules has become more important for thoracoscopic wedge resection and sequential lobectomy 1,2 . We have previously reported that transbronchial injection of a dye mixture of indigo carmine and Lipiodol can be a good method for preoperative marking of the visceral pleura 11,15 . In the present study, using a porcine model, we demonstrated that this dye mixture, injected using a bronchoscope and spray catheter, remained on the visceral pleura for up to 24 h and could be detected with the naked eye.…”
Section: Discussionsupporting
confidence: 54%
“…This article ( 1 ) titled “Evaluation of factors affecting the visualization of dye after transbronchial dye injection: an animal experiment” (doi: 10.21037/atm-20-1695), unfortunately contains an error in author’s affiliation 2.…”
mentioning
confidence: 99%